Assessing applied protection across the world - Bouët, Antoine; Decreux, Yvan; Fontagné, Lionel; Jean, Sébastien; Laborde Debucquet, David (Wiley, 2008)
This paper presents MAcMap–HS‐6, a database providing a consistent, ad valorem equivalent measure of tariff duties and tariff rate quotas for 163 countries and 208 partners, at the six‐digit level of the Harmonized System (5111 products), accounting for all preferential agreements. We describe the methodology used to compute and aggregate an ad valorem equivalent of applied protection. Emphasis is placed on minimizing the endogeneity bias in the aggregation procedure, while acknowledging structural differences in export specialization. The resulting quantitative assessment is illustrated by giving an overview of applied protection across the world in 2001, in terms of average as well as distribution.